Dental implants: Surface modification of cp-Ti using plasma spraying and the deposition of hydroxyapatite - Oliveira, Vercik L.C. [UNESP]; Alencar, A. C. [UNESP]; Ramires, I. [UNESP]; Guastaldi, Antonio Carlos [UNESP] (Trans Tech Publications, 2003)
The commercial pure titanium (cp-Ti) is currently being used with great success in dental implants. In this work we investigate how the cp-Ti implants can be improved by modifying the metal surface morphology, on which a synthetic material with properties similar to that of the inorganic part of the bone, is deposited to facilitate the bone/implant bonding. This synthetic material is the hydroxyapatite, HA, a calcium-phosphate ceramic. The surface modification consists in the application of a titanium oxide (TiO2) layer, using the thermal aspersion - plasma spray technique, with posterior deposition of HA, using the biomimetic method. The X-ray diffraction (XRD), Scanning Electron Microscopy (SEM) with Energy Dispersive X-ray (EDX) and Diffuse Reflectance Infrared Fourier Transform (DRIFT) techniques have been used for characterizing phases, microstructures and morphologies of the coatings. The TiO2 deposit shows a mixture of anatase, rutilo and TiO2-x phases, and a porous and laminar morphology, which facilitate the HA deposition. After the thermal treatment, the previously amorphous structured HA coating, shows a porous homogeneous morphology with particle size of about 2-2.5 μm, with crystallinity and composition similar to that of the biological HA.
Keywords: Biomaterials; Hydroxyapatite; Surface modification; Titanium oxide; Biomimetic method; Calcium phosphate ceramic; Diffuse reflectance infrared Fourier transform; Bone; Deposition; Energy dispersive spectroscopy; Fourier transform infrared spectroscopy; Morphology; Plasma spraying; Scanning electron microscopy; Surface treatment; Titanium; Titanium dioxide; X ray diffraction analysis; Dental prostheses